Mythological realism of Anatoly Kim as a construct of the schism - Safronova, Ludmila; Zhanysbekova, Elmira (Przegląd Wschodnioeuropejski, 2018)
The article, in the psychoanalytic and cognitive aspect explores the principle of constructing the poetics of a grotesque novel by Anatoly Kim “Centaur settlement”. The novel is based on the connection of the incompatible, the synthesis of contradictions, characteristic of the schizophrenic schism: namely, mythological realism, man/beast, nomad/agriculturist, hysteria/obsession, the Christian archetype of God – the punisher/rescuer, etc. The appeal to the author’s myth has the function of neutralizing oppositions, “escaping into health” – to a holistic worldview of a person and society.